Search Friction in the U.S. Labor Market - Audra J. Bowlus; Shannon N. Seitz (Tinbergen Institute, 1998)
In this paper we determine the feasibility of using data from thePanel Study of Income Dynamics to estimate the Burdett-Mortensengeneral equilibrium search model. The data contain sufficientinformation on wages, labor force states, durations, and transitionsto generate estimates of the model's structural parameters. Ouranalysis compares the relative labor market search friction forblack and white male household heads. In general we find blacks facegreater search friction while unemployed than whites, but a similarlevel while employed. Within the model this finding impliessubstantial productivity differentials are needed to generate theblack-white wage differentials found in the data.
Keywords: 330; Arbeitsmarkt; Arbeitsuche; Informationskosten; Theorie; USA